Repeated-sprint training in hypoxia induced by voluntary hypoventilation in swimming - Trincat, L.; Woorons, X.; Millet, G. P. (International Journal of Sports Physiology and Performance, 2017)
Purpose: Repeated-sprint training in hypoxia (RSH) has been shown as an efficient method for improving repeated-sprint ability (RSA) in team-sport players but has not been investigated in swimming. We assessed whether RSH with arterial desaturation induced by voluntary hypoventilation at low lung volume (VHL) could improve RSA to a greater extent than the same training performed under normal breathing (NB) conditions.